2017
DOI: 10.1021/acsinfecdis.7b00194
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate Alters Bacterial Susceptibility to Antibiotics by Targeting the Proton Motive Force

Abstract: The antibacterial properties of sodium bicarbonate have been known for years, yet the molecular understanding of its mechanism of action is still lacking. Utilizing chemical-chemical combinations, we first explored the effect of bicarbonate on the activity of conventional antibiotics to infer on the mechanism. Remarkably, the activity of 8 classes of antibiotics differed in the presence of this ubiquitous buffer. These interactions and a study of mechanism of action revealed that, at physiological concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
133
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(146 citation statements)
references
References 48 publications
8
133
1
4
Order By: Relevance
“…2). To probe the possibility that CBG selectively dissipated membrane potential (Δψ) component of proton motive force, we tested for synergy with sodium bicarbonate, a known perturbant of ΔpH, that has been shown to synergize with molecules that reduce Δψ 25 . A lack of synergy between these compounds suggested CBG disrupts the integrity of the cytoplasmic membrane (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). To probe the possibility that CBG selectively dissipated membrane potential (Δψ) component of proton motive force, we tested for synergy with sodium bicarbonate, a known perturbant of ΔpH, that has been shown to synergize with molecules that reduce Δψ 25 . A lack of synergy between these compounds suggested CBG disrupts the integrity of the cytoplasmic membrane (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All of these components modulate various pathways and are mainly causative for the altered in vivo efficiency of antibiotics. [77,78] Despite these advancements of in vitro AST,t he full complexity of bacterial infections in vivo can hardly be simulated. [75,76] Ar ecent study by Ersoy et al revealed that the antibiotic susceptibility of various clinical isolates strongly depends on the medium used for in vitro cultivation.…”
Section: Screening Platformsmentioning
confidence: 99%
“…[77] Similarly, the addition of physiological concentrations of NaHCO 3 to standard MHB medium resulted in ah ost-mimicking environment, which suggests that the salt is akey component that contributes to antibiotic susceptibility in vivo. [77,78] Despite these advancements of in vitro AST,t he full complexity of bacterial infections in vivo can hardly be simulated. Therefore,h igh-throughput infection screening has become av aluable tool, especially for secondary antibiotic screens.…”
Section: Screening Platformsmentioning
confidence: 99%
“…All diese Komponenten regulieren zahlreiche bakterielle Stoffwechselwege und sind der Hauptgrund füreine veränderte Invivo-Effizienz von Antibiotika. [77,78] Tr otz der beschriebenen Fortschritte des In-vitro-AST kann die volle Komplexitätd er bakteriellen Infektion in vivo jedoch kaum simuliert werden. Ein leicht umsetzbarer und sehr effektiver Ansatz ist die Substitution von geläufigen Vollmedien durch Minimalmedien.…”
Section: Screening-plattformenunclassified
“…[75,76] [77] In ähnlicher Weise führte die Zugabe von physiologischen Konzentrationen von NaHCO 3 zum geläufigen MHB-Medium zu einer Wirt-ähnlichen Umgebung.D as Salz scheint somit eine entscheidende Komponente fürdie Antibiotika-Empfindlichkeit in vivo zu sein. [77,78] Tr otz der beschriebenen Fortschritte des In-vitro-AST kann die volle Komplexitätd er bakteriellen Infektion in vivo jedoch kaum simuliert werden. Hochdurchsatz-Infektions-Screenings haben sich daher heute zu einer wertvollen Methode,i nsbesondere fürs ekundäre Antibiotika-Screenings, entwickelt.…”
Section: Screening-plattformenunclassified